The Earliest Chinese Proto-Porcelain Excavated from Kiln Sites: An Elemental Analysis - Li, Yu; Zhang, Bin; Cheng, Huansheng; Zheng, Jianming (PLOS ONE, 2015)
In June 2012, the Piaoshan kiln site was excavated in Huzhou, Zhejiang Province, which hitherto proved to be the earliest known Chinese proto-porcelain kiln. Judging from the decorative patterns of unearthed impressed stoneware and proto-porcelain sherds, the site was determined to date to the late Xia (c. 2070–c. 1600 BC), the first dynasty of China. Here, we report on proton-induced X-ray emission analyses of 118 proto-porcelain and 35 impressed stoneware sherds from Piaoshan and five subsequent kiln sites in the vicinity. Using principal components analysis on the major chemical compositions, we reveal the relationships between impressed stoneware and proto-porcelain samples from the six kiln sites. The sherds from different sites have distinctive chemical profiles. The results indicate that the raw materials were procured locally. We find a developmental tendency for early glazes towards mature calcium-based glaze. It is most likely that woody plant ashes with increased calcia-potash ratios were applied to the formula.